The effect of CHIN-SKIP sports game intervention on motor ability in preschool children aged 5–6 years - Zhang, Shiqing; Liu, Min; Sun, Jianhang; Chong, Jianxiang; Ma, Jiahua (Frontiers in Public Health, 2025)
IntroductionTo evaluate the efficacy of CHIN-SKIP sports game intervention in enhancing motor ability among preschool children aged 5–6 years.MethodsFrom September to December 2024, a total of 60 preschool children (aged 5–6 years) were randomly selected from two large classes at DM kindergarten and equally allocated to either the experimental group (n = 30) or control group (n = 30), with balanced gender distribution between groups. The experimental group received the CHIN-SKIP sports game intervention, while the control group participated in standard kindergarten physical activities. The 12-week intervention consisted of two 30-min sessions per week. Motor ability was assessed pre- and post-intervention using the “Manual for Testing Motor Ability in Children Aged 3–6 Years” developed by the China Institute of Sports Science (CISS), which evaluates five distinct domains of motor ability.ResultsMixed ANOVA revealed significant main effects of both group assignment and time on motor ability outcomes (all p < 0.01). The experimental group demonstrated superior performance in total motor quotient (TMQ) and gross motor quotient (GMQ) compared to controls (p < 0.01). Temporal improvements were observed across all measures (p < 0.01), with TMQ and GMQ showing the most pronounced enhancements. Significant group × time interactions (p < 0.001) indicated greater improvement in the experimental group for all measures except visual-motor integration.ConclusionThe CHIN-SKIP sports game intervention effectively enhances motor ability in 5-6-year-old preschool children and shows promise for broader implementation in preschool children education settings, thereby establishing a strong foundation for developmental progress.